2011
DOI: 10.1080/19388071003731554
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Parental Involvement in Reading and Schooling and Children's Reading Engagement in Latino Families

Abstract: This study focused on the link between parental involvement in reading and schooling and children's reading motivation. The sample consisted of 128 low-income Latino students in the second through seventh grade and their immigrant parents. The specific questions addressed were: (1) How involved are Latino parents in their children 's schooling and reading? and (2) What is the association between Latino parents' involvement in their children's schooling and reading and their children's reading engagement? Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Also, aspects that are more directly related to the child's reading should be taken into account (e.g., parent-child communication about reading, parents' interest in their child's reading, etc. ; Loera, Rueda, & Nakamoto, 2011). More systematic analyses that include further aspects of parental involvement are thus necessary to unveil potential mediation effects.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Also, aspects that are more directly related to the child's reading should be taken into account (e.g., parent-child communication about reading, parents' interest in their child's reading, etc. ; Loera, Rueda, & Nakamoto, 2011). More systematic analyses that include further aspects of parental involvement are thus necessary to unveil potential mediation effects.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Language friendly classrooms also may increase parental capacity to take advantage of school-based early literacy and math learning resources, which is particularly important given what we know about the role families play in supporting young children's development in these areas (Loera, Rueda, & Nakamoto, 2011;C. O. Lopez & Donovan, 2009).…”
Section: Impact Of School Linguistic Capacity On Parental Involvementmentioning
confidence: 99%
“…In a previous study, I explored elementary ELs' reading motivation and found that ELs who were motivated readers wanted to read English texts because of social motivation, instrumental motivation, and high levels of perceived competence (Protacio, 2012). Given the research that has shown reading motivation (an integral part of reading engagement) steeply declines when students transition to the middle grades (e.g., McKenna et al, 2012), I wanted to know more about how ELs' reading engagement might change in a middle level setting.Despite the promise of improving reading engagement as a way to facilitate ELs' reading achievement, there have only been a few studies conducted on this topic (Arzubiaga, Rueda, & Monzo, 2002;Ivey & Broaddus, 2007;Loera et al, 2011;Robinson, 2010;Sturtevant & Kim, 2010 …”
mentioning
confidence: 99%